Greening Arctic Cruise Shipping Through Law and Technology:A Role for China - Kirchner, Stefan (2018)
Increased shipping in the Arctic will mean not only increasing tourism revenue for local communities but, more importantly in the long run, increasing health risks for local residents. The overwhelming majority of ships is powered with fossil fuels and concerns over emissions have led to the creation of Emission Control Areas, such as the Sulphur Emissions Control Area (SECA) in the Baltic Sea, the North Sea and along much, but not all, of the coasts of the United States and Canada. None of the existing SECAs includes areas north of the Arctic Circle. This means that coastal communities, in particular in cruise ship destinations, are put at risk from high emissions of SO2. The research presented here shows that China has the potential to play several roles in contributing to the protection of coastal communities in the Arctic and in safeguarding the human right to live in a healthy environment, which has long been recognized by the European Court of Human Rights. It will be shown that China has the potential to use international forms of cooperation in the context of the work of the International Maritime Organization in order to support the establishment of a SECA for the entire Arctic Ocean but can also profit from it in the long run, provided that China’s shipbuilding industry becomes able to meet the needs of more environment conscious ship buyers.